2016
DOI: 10.1111/acer.13210
|View full text |Cite
|
Sign up to set email alerts
|

FAAH Gene Variation Moderates Stress Response and Symptom Severity in Patients with Posttraumatic Stress Disorder and Comorbid Alcohol Dependence

Abstract: BACKGROUND A common single nucleotide polymorphism (C385A) in the human fatty acid amide hydrolase (FAAH) gene has been associated with decreased distress responses in healthy volunteers, but its role in psychiatric disorders remains unknown. Here, we obtained genotypes and carried out a secondary analysis of subjects from a trial of comorbid posttraumatic stress disorder (PTSD) and alcohol dependence (AD). We evaluated the effects of C385A variation on behavioral and biochemical biomarkers of distress respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 63 publications
6
52
2
Order By: Relevance
“…These emotional states, and the search for the anxiolytic and antidepressant-like effects of alcohol, might in turn contribute to promoting the high levels of alcohol intake and preference that characterize the escalation drinking observed in the present study in mice [Colombo et al 1995; Koob and Volkow 2010]. The stress-response eCB system is critically involved in “anxiety”-related behaviors [Dincheva et al 2015; Parsons & Hurd 2015; Pardini et al et al 2012; Spagnolo et al 2016], and FAAH inhibition reverses enhanced anxiety-like behavior present during alcohol withdrawal [Cippitelli et al 2008]. Our mouse escalation model suggests a role for FAAH activity in the alcohol withdrawal-induced tendency of mice towards “anxiety”- and “depression”- like states.…”
Section: Discussionmentioning
confidence: 99%
“…These emotional states, and the search for the anxiolytic and antidepressant-like effects of alcohol, might in turn contribute to promoting the high levels of alcohol intake and preference that characterize the escalation drinking observed in the present study in mice [Colombo et al 1995; Koob and Volkow 2010]. The stress-response eCB system is critically involved in “anxiety”-related behaviors [Dincheva et al 2015; Parsons & Hurd 2015; Pardini et al et al 2012; Spagnolo et al 2016], and FAAH inhibition reverses enhanced anxiety-like behavior present during alcohol withdrawal [Cippitelli et al 2008]. Our mouse escalation model suggests a role for FAAH activity in the alcohol withdrawal-induced tendency of mice towards “anxiety”- and “depression”- like states.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alcohol-dependent patients with the C allele exhibit enhanced PFC, orbitofrontal cortex, and NAc activation in response to alcohol-associated cues and report larger subjective reward following the consumption of several alcoholic beverages (Hutchison et al, 2008). In addition, the CNR1 C allele (Marcos et al, 2012) and the FAAH C385A single nucleotide polymorphism (Buhler et al, 2014;Spagnolo et al, 2016) have been identified as likely indicators of individuals who are at higher risk for alcohol abuse. Furthermore, the FAAH Pro129Thr missense variant (rs324420) has also been shown to be associated with alcohol dependence severity in European Americans (Sloan et al, 2018).…”
Section: The Ecb System and Susceptibility To Audsmentioning
confidence: 99%
“…Altered FAAH enzyme activity has been directly linked to neurological changes that increase excitability and anxiety (Gunduz-Cinar et al, 2013). Furthermore, the specific genetic variant of FAAH assayed in our study (rs324420) has been previously associated with several anxiety disorders, particularly in association with psychosocial stress (Lazary et al, 2016;Spagnolo et al, 2016).…”
Section: Introductionmentioning
confidence: 59%
“…FAAH has been previously associated with psychosocial stress and anxiety, for which we have multiple measures including generalized scales developed for use globally (PSS) and specialized scales designed for use in the region (HD and AYMH; Spagnolo et al, 2016). However, few studies have linked FAAH specifically with childhood trauma, Lazary et al (2016) being the notable exception that led us to assay the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation